Hydrothermal Synthesis and Structure of Phenanthroline Manganese(II) Complex - Pi, Zong-Xin; Bi, Jian-Hong; Dong, Hua-Ze (Asian Journal of Chemistry, 2015)
A new manganese(II) complex with the m.f. C30H20N10O2Mn2 was synthesized by hydrothermal reaction and characterized by IR spectra and single crystal X-ray diffraction. The crystal is in a Monoclinic system, space group C2/c with unit cell parameters: a = 16.8439(15)Å, b = 13.9842(12)Å, c = 14.4033(14)Å, a = 90º, b = 109.1090(10)º, g = 90º, V = 3205.7(5)Å3, Z = 4, Mr = 662.44, Dc = 1.373 Mg/cm3, μ = 0.831 mm-1, F(000) = 1344, T = 298(2) K, R = 0.0625, wR = 0.1507 for 7979 reflections with I > 2s(I). The crystal structure analysis shows that the manganese(II) is a six-coordinated in a slightly distorted octahedron environment.